Role of Modern Dance Extracurricular Activities in Developing Students’ Movement Creativity - Jessika Priskila; Utami Arsih (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2026)
This study aims to describe the implementation and role of the modern dance extracurricular activity in developing students movement creativity at one of senior high schools in Semarang. The research uses a descriptive qualitative approach. Data collection techniques include observation, interviews, and documentation. The participants included sixteen students observed during extracurricular activity, while in-depth interviews were conducted with the leader, secretary, and coach. The research results show that extracurricular activities are conducted regularly through several training stages. These stages include warming up, repetition of movement material, exploration of movement variations, and choreography preparation for performance needs. The training process gives students the opportunity to explore movement ideas, improvise, and create movement variations both independently and in groups. This activity encourages the development of students movement creativity through the ability to combine various dance styles and creatively process accompanying music. In addition, the modern dance extracurricular activity also helps to enhance students’ self-confidence, responsibility, and teamwork skills. The modern dance extracurricular activity serves as and effective platform for students to develop their movement creativity while also supporting their social and psychological development.